Pengasuhan Berbasis Neurosain dan Kecerdasan Emosi dalam Pengasuhan Anak Usia Dini - Riyadlotus Sholichah (Prodi Pendidikan Islam Anak Usia Dini Institut Agama Islam Daruttaqwa Gresik, 2020)
Early childhood is a critical period for developing emotional abilities. Emotional intelligence is one of the crucial pillars in early childhood development. Crucial because this intelligence will greatly affect a person's behavior throughout life until adulthood. This intelligence is also very influential on the success or failure of someone in his life in the future. Many parents or educators believe that cognitive intelligence, or better known as cognitive intelligence, is more important than emotional intelligence (Emotional Intelligence) for children. Until much we see various systems and models of learning or education competing to design the best stimulation on the development of this cognitive potential. Although cognitive development is important at this age of development, the emotional stage of the child's achievement also plays an important role, which has a large influence on other aspects of development. At this age children are also learning to develop their self-concept as competent and confident individuals. The family, as the main pillar of caregiving will be very instrumental in its development. Neurosain-based early childhood emotional development, are educational efforts undertaken by parents or educators, including activities to hone, love and nurture (hone, foster) children who stand and use the basics of brain behavioral science (neurons). It is very important for every educator, be it a teacher, parents and caregivers to understand and understand how the child's brain and his brain work. Also how a child's brain grows and develops in a basic way. In early childhood, in order to be able to know themselves before establishing relationships with friends or others, children need to understand the basics of emotions called primary emotions. Primary emotions are the basic emotions that humans have had since they were born. Types of primary emotions generally include fear (fear), anger (anger), sad (sadness), happy (joy), surprise (surprise), disgust (disgust) and resentful (contempt). The limbic system, as an emotional control system in adults and early childhood, one of its main circuits is the amygdala. Amygdala is able to remember emotional events very well. Even though the system works under an unconscious response, the amygdala is able to remember emotional events that are experienced and serve as a behavioral reference if similar events occur at different times.